Analisis Pengungkapan Triple Bottom Linedan Faktor yang Mempengaruhi; Lintas Negara Indonesia dan Jepang - Sandra Aulia Zanny; Idris Kartawijaya (Program Pendidikan Vokasi Universitas Indonesia, 2013)
ABSTRACT.Current firm performance is not only measured by economic term (single bottom line) but alsoby social and environmental (triple bottom line). Purposes of this research are analyzing of TBL disclosureand influences factors, by using sample of companies in Indonesia and Japan.This paper investigates Triple Bottom Line (TBL) disclosure of 50 of the largest Indonesian andJapanese companies by using secondary data. Twenty two disclosure criteria were developed for each of theTBL disclosure areas: economic, social, and enviromental. Disclosure information was examined in annualreports, separate or stand-alone report and company‟s website. Regression analysis has been used to examinethe determinants of TBL disclosure practice empirically.Our result indicated that, for total of TBL disclosure (combining economic, social and environmentalcatagories), the extent of reporting is higher for firm with larger size and higher liquidity, and special forenvironmental disclosure for firm with membership in the manufacturing industry for Indonesian companies.Futher analysis indicated that the results of the total TBL disclosure are primarily driven by non-economicdisclosures. We also found that the extent of overall TBL disclosure is higher for Japanese firms, withenvironmental disclosure being the main key. This result could be attributed to the different national culturesand to the regulation environment between Indonesian and Japan.Keywords: TBL, economic, social, environment, Indonesia, Japan